The Influence of Emotional Intelligence and School Environment on Teacher Job Satisfaction at SMKN (State Vocational Schools) in Sub Rayon I at Sambas Regency - Auful Amsyari; Usman Radiana; Aswandi Aswandi (JETL (Journal of Education, Teaching and Learning), 2019)
Job satisfaction in this study is the feelings and reactions of individuals who appear in the form of a positive attitude towards their work. Theoretically, the emotional intelligence of the principal and the school environment will affect teacher job satisfaction. The problems in this study are as follows: 1) Is there an influence of the principal's emotional intelligence on the job satisfaction of teachers in State Vocational Schools in Sub District I Sambas Regency? 2) Is there any influence of the school environment on the job satisfaction of teachers of State Vocational Schools in Sambas Sub-District I? 3) Is there an influence between the principal's emotional intelligence and the school environment together on the job satisfaction of teachers of State Vocational Schools in Sub District I Sambas Regency? The purpose of this study was to reveal the influence of the principal's emotional intelligence on teacher job satisfaction, school environment on the work satisfaction of teachers and emotional and emotional intelligence and school environment together on the job satisfaction of teachers of Sub District I Sub District of Sambas Regency. This study uses a quantitative approach. The population in this study amounted to 89 teachers. While the sample used was 73 teachers. Data collection instruments in the form of questionnaires and data analysis using descriptive statistics and inferential statistics. The results of the study were: 1) the influence of the principal's emotional intelligence (X1) on teacher job satisfaction by 0.301 or 30%, 2) the influence of the school environment (X2) on teacher job satisfaction (β1) by 0.06 or 6%, 3) the influence of the principal's emotional intelligence (X1) and school environment (X2) together on teacher job satisfaction (Y) of 0.311 or 31%. The conclusion of this study: 1) emotional intelligence has a significant effect on teacher job satisfaction, 2) the school environment has a significant effect on teacher job satisfaction, and 3) the principal's emotional intelligence and school environment together have a significant effect on the job satisfaction of vocational teachers Negeri Sub Rayon I Sambas Regency. The recommendation given from the results of this study is that teachers need to reveal how to increase their job satisfaction so that they love their profession more.Job satisfaction in this study is the feelings and reactions of individuals who appear in the form of a positive attitude towards their work. Theoretically, the emotional intelligence of the principal and the school environment will affect teacher job satisfaction. The problems in this study are as follows: 1) Is there an influence of the principal's emotional intelligence on the job satisfaction of teachers in State Vocational Schools in Sub District I Sambas Regency? 2) Is there any influence of the school environment on the job satisfaction of teachers of State Vocational Schools in Sambas Sub-District I? 3) Is there an influence between the principal's emotional intelligence and the school environment together on the job satisfaction of teachers of State Vocational Schools in Sub District I Sambas Regency? The purpose of this study was to reveal the influence of the principal's emotional intelligence on teacher job satisfaction, school environment on the work satisfaction of teachers and emotional and emotional intelligence and school environment together on the job satisfaction of teachers of Sub District I Sub District of Sambas Regency. This study uses a quantitative approach. The population in this study amounted to 89 teachers. While the sample used was 73 teachers. Data collection instruments in the form of questionnaires and data analysis using descriptive statistics and inferential statistics. The results of the study were: 1) the influence of the principal's emotional intelligence (X1) on teacher job satisfaction by 0.301 or 30%, 2) the influence of the school environment (X2) on teacher job satisfaction (β1) by 0.06 or 6%, 3) the influence of the principal's emotional intelligence (X1) and school environment (X2) together on teacher job satisfaction (Y) of 0.311 or 31%. The conclusion of this study: 1) emotional intelligence has a significant effect on teacher job satisfaction, 2) the school environment has a significant effect on teacher job satisfaction, and 3) the principal's emotional intelligence and school environment together have a significant effect on the job satisfaction of vocational teachers Negeri Sub Rayon I Sambas Regency. The recommendation given from the results of this study is that teachers need to reveal how to increase their job satisfaction so that they love their profession more.